Benchmarking marine renewable energy technologies through LCA: Wave energy converters in the Mediterranean - Bruno, Morena; Maccanti, Matteo; Pulselli, Riccardo Maria; Sabbetta, Alessio; Neri, Elena; Patrizi, Nicoletta; Bastianoni, Simone (Frontiers in Energy Research, 2022)
The present work evaluates the environmental performance of three Wave Energy Converters including on-shore Oscillating Water Columns and Oscillating Floaters embedded in piers, and near-shore seabed-based buoys, in the Mediterranean Basin. The Life Cycle Assessment methodology was used to account for their potential environmental impact, in terms of Carbon Footprint (t CO2eq), considering four main phases, i.e., manufacturing of material components, assembling and installation on site, maintenance in time, decommission end of life. Results show the greenhouse gas emission from different lifecycle processes, based on the inventory of main energy inputs and materials, highlighting the major impact of the manufacture of the structural components (52%), especially due to the limited durability of materials. In order to compare performances of the three different Wave Energy Converters, the Carbon Intensity of Electricity was evaluated considering a range of electricity production per each technology based on data available on scientific literature. Results obtained for single device (203 - 270 g CO2eq‧kWh-1 for Oscillating Water Column system; 94 - 374 g CO2eq‧kWh-1 for Oscillating Floater and 105 - 158 g CO2eq‧kWh-1 for the seabed-based buoy) highlight that Wave Energy Converters are promising solutions to harvest wave energy, showing lower Carbon Intensity of Electricity values compared to fossil energy sources; nevertheless technological improvements are needed to increase efficiency and achieve performances of other renewable energy sources. Moreover, the combination of Wave Energy Converters with other solutions, such as offshore wind turbines, represents a valuable option in the future to increase productivity and foster energy transition of Mediterranean regions.